ACADEMIC PROCRASTINATION IN STUDENTS: A SLR REVIEW - Nailah Rizqia Azhar; Abdul Kholiq; Dodi Suryana (OPTIMA: Journal Of Guidance and Counseling, 2023)
Procrastination is Thing urgent for researched because influence pattern think and Act individual in take decision . Purpose study this for study study procrastination with systematic literature review method of 15 journals from 214 databases. As for results study about things that cause someone to do academic procrastination, forms procrastination, teacher strategy bk reduce behavior procrastination , and procrastination conducted by student also.